1993
DOI: 10.2337/diab.42.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-Induced Increase in Mesangial Cell Prostaglandin Release: Effect of Hyperglycemia and PKC Inhibition

Abstract: Glomerular accumulation of extracellular matrix in diabetes is a potential regulator of mesangial cell-matrix interactions through transmembrane matrix receptors. We now provide evidence that PG production from rat glomerular mesangial cells is increased by Fn. An increase in PG (measured as PGE) was demonstrated in mesangial cell-enriched glomerular cores after 1-h exposure (149 +/- 8% of timed control) and was sustained over a 24-h period (214 +/- 7%). Increased PG production followed exposure to a chymotryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…These effects of pioglitazone on cell viability, calcium channel, and angiotensin II receptor may explain the suppression of the angiotensin II-induced cellular contraction at the higher concentration of the drug. The role of prostaglandin E2 on the reduced contractile response of mesangial cells in high glucose has been reported, since prostaglandin E2 decreases mesangial cell tonicity, and an increased production of prostaglandin E2 by mesangial cells in high glucose has also been reported [52,53]. The concentrations of indomethacin and acetyl salicylic acid used in our study were sufficiently high to suppress prostaglandin synthesis [54,55]; however, only indomethacin as a PPARc ligand could attenuate the reduced contractile response.…”
Section: Discussionmentioning
confidence: 53%
“…These effects of pioglitazone on cell viability, calcium channel, and angiotensin II receptor may explain the suppression of the angiotensin II-induced cellular contraction at the higher concentration of the drug. The role of prostaglandin E2 on the reduced contractile response of mesangial cells in high glucose has been reported, since prostaglandin E2 decreases mesangial cell tonicity, and an increased production of prostaglandin E2 by mesangial cells in high glucose has also been reported [52,53]. The concentrations of indomethacin and acetyl salicylic acid used in our study were sufficiently high to suppress prostaglandin synthesis [54,55]; however, only indomethacin as a PPARc ligand could attenuate the reduced contractile response.…”
Section: Discussionmentioning
confidence: 53%
“…Our previous data have shown that mesangial cores can respond to soluble fibronectin with an increased production of P G E [8], and in other cultured cell types plated onto fibronectin elevated tyrosine phosphorylation of FAK has been demonstrated [13,14]. We now show that cultured mesangial cells plated for 2 h onto fibronectin-coated plates have increased P G E production (from 12.76+1.83 to 24.52 + 1.10 ng-2 h -1 9 dish -1 p < 0.05, n = 3) and also increased tyrosine phosphorylation of FAK ( Fig.…”
Section: Results Are Representative Of Two Individual Experimentsmentioning
confidence: 96%
“…The increase in mesangial matrix probably contributes to the structural changes observed in the diabetic kidney, however, the effect of matrix proteins on cellular function may also be important and must be considered. One of the early biochemical changes to occur in the diabetic kidney is the increased production of prostaglandins [5], shown by previous studies to be consequent on hyperglycaemia-induced protein kinase C activation [6][7][8], and we have shown, in vitro, that the addition of exogenous fibronectin to glomerular cores or isolated mesangial cells also results in increased production of prostaglandins [8]. Matrix proteins, including fibronectin, signal to cells via transmembrane cell surface receptors (integrins).…”
mentioning
confidence: 73%
See 2 more Smart Citations